2016
DOI: 10.1111/bjd.14475
|View full text |Cite
|
Sign up to set email alerts
|

Development of core outcome sets in hidradenitis suppurativa: systematic review of outcome measure instruments to inform the process

Abstract: SummaryThe recent hidradenitis suppurativa (HS) Cochrane review identified outcome measure heterogeneity as an important issue to address when designing future HS trials. Our objective was to follow the Harmonising Outcome Measures for Eczema (HOME) roadmap, by performing a systematic review of HS outcome measure instruments to inform the development of an HS core outcome set. We performed a systematic review to identify validation evidence for outcome measure instruments used in HS randomized controlled trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
111
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(121 citation statements)
references
References 32 publications
1
111
0
1
Order By: Relevance
“…Until now, clinical studies in HS have measured QOL with either dermatologic-specific or generic questionnaires [11, 15]. Generic instruments are designed to cover a wide range of dimensions and to be applicable in a wide range of conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until now, clinical studies in HS have measured QOL with either dermatologic-specific or generic questionnaires [11, 15]. Generic instruments are designed to cover a wide range of dimensions and to be applicable in a wide range of conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, QOL can be measured with different types of outcome measurement instruments. Dermatologic-specific QOL instruments, such as Dermatology Life Quality Index (DLQI) [13] and Skindex [14], were used to measure QOL in several HS trials [15]. These instruments, however, were developed with the broader dermatologic patient in mind, and the instruments may not capture changes in QOL particularly affected in HS.…”
Section: Introductionmentioning
confidence: 99%
“…For HS, however, reported outcome measures are numerous with a total of 30 outcome measure instruments in the 12 RCTs included in a recent systematic review. 15 No consensus on core outcomes for HS exists. Researchers therefore use various instruments, which may or may not be representative.…”
Section: Current Selection Of Outcomes For Use In Clinical Trials On mentioning
confidence: 99%
“…The Hidradenitis Suppurativa Clinical Response (HiSCR) is defined as a 50% or more reduction in inflammatory lesion count and no increase in abscesses or draining fistulas when compared with baseline 19. A review of the outcome measures used in clinical trials of HS identified 30 assessment measures, of which 27 lacked any validation data 20. The HiSCR was found to be supported by good quality validation data, but had several deficiencies, including the lack of a definition of a minimal clinically important difference.…”
Section: Clinical Efficacymentioning
confidence: 99%